2017
DOI: 10.3892/ol.2017.6737
|View full text |Cite
|
Sign up to set email alerts
|

High excision repair cross-complementation group 1 expression is associated with favorable prognostic factors in breast cancer

Abstract: Abstract. Distortion of DNA can inhibit transcription and replication, resulting in cell death. The nucleotide excision repair (NER) pathway recognizes and repairs DNA adducts. Excision repair cross-complementation group 1 (ERCC1) is a nuclease that serves a vital role in the NER pathway. Few studies have investigated ERCC1 expression in breast cancer. The aim of the present study was to analyze the association between clinicopathological features and ERCC1 expression in breast cancer. ERCC1 expression was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A positive correlation was found between ERCC1 mRNA expression and DNA repair capacity in several studies [ 15 , 16 ]. The expression of ERCC1 was increased by cisplatin treatment in a time- and a dose-dependent manner in ovarian cancer cell lines [ 17 ]. However, the expression level of ERCC1 may have a dual function in breast carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation was found between ERCC1 mRNA expression and DNA repair capacity in several studies [ 15 , 16 ]. The expression of ERCC1 was increased by cisplatin treatment in a time- and a dose-dependent manner in ovarian cancer cell lines [ 17 ]. However, the expression level of ERCC1 may have a dual function in breast carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings about ERCC1 seemed not to be fully in accordance with the previous studies in breast cancer. Similarly, Kim et al [ 20 ] reported that high expression of ERCC1 was statistically associated with lower T stage, lower tumor size, no lymph node metastasis, positive ER and PR expression status, non-TNBC, and no lymphovascular invasion. By contrast, there was no association between ERCC1 expression and clinicopathological parameters, including age, histology, tumor stage at diagnosis, hormonal receptors (ER, PR) status, HER-2 status, presence of visceral disease, and pretreatment of metastatic disease, which has been studied by Metro et al [ 35 ] who analyzed ERCC1 expression using an automated and quantitative immunofluorescence technique.…”
Section: Discussionmentioning
confidence: 94%
“…High expression of ERCC1 is associated with favorable prognostic parameters such as a positive ER expression status in breast cancer. [ 20 ] In vitro experiment, RRM1 gene silencing can reverse paclitaxel resistance in human breast cancer cell line MCF-7/R. [ 21 ] Elevated TYMS expression was a detrimental factor for pemetrexed treatment in advanced breast cancer, indicating that it may be a biomarker to choose chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%
“…15 Higher expression of ERCC1 was found to be associated with favorable prognostic factors for early stage breast cancer patients, but with poor outcome for those metastatic triple negative breast cancer patients treated with platinumbase chemotherapy. 16 This reminds us the complex regulation of ERCC1 in real world scenario of breast and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%